DEVELOPMENT OF ARTISTIC AND CREATIVE ABILITIES OF FUTURE TEACHERS OF FINE ARTS THROUGH COMPUTER GRAPHICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the issues of improving the system of art education with the help of computer systems and their software. The authors recommend techniques for using computer graphics in the process of art education. These methods open up ample opportunities for future teachers of visual arts for creative expression in the creation of graphic animated works and in the preparation of sketches in the classical styles of visual and decorative arts.